Keefektifan Beberapa Spesies Cendawan Entomopatogen untuk Mengendalikan Rayap Tanah Coptotermes gestroi WASMANN (Isoptera: Rhinotermitidae) dengan Metode Kontak dan Umpan Effectiveness of Some Entomopathogenic Fungi Species as Bio-control Agent to Subterranean Termite Coptotermes gestroi WASMANN (Isoptera: Rhinotermitidae) Using Contact and Baiting Methods - Desyanti Desyanti; Yusuf Sudo Hadi; Sulaeman Yusuf; Teguh Santoso (Jurnal Ilmu dan Teknologi Kayu Tropis, 2007)
Species of entomopathogenic fungi, i.e. Metarhizium anisopliae (Metsch.) Sorokin, Metarhizium brunneum Petch, Beauveria bassiana (Bals.) Vuillemin, Fusarium oxysporum Link and Aspergillus flavus Link were tested their effectiveness as bio-control against to subterranean termite Coptotermes gestroi Wasmann. Pure culture of each fungal species was stored in 40C. Before used, those fungi were recultured in Sabouraud Dextrose Agar with Yeast Extract (SDAY) media and incubated in 240C and RH 95% for 3 weeks. The series of conidial density has been used (0, 107, 5x106, 106, 5x105 and 105 conidia/ml) for pathogenicity test. The LC95 of M. brunneum was used for contact and baiting methods and the bioassay was repeated four times. The data was analyzed using ANOVA and with DNMRT. The lethal concentration (LC) and lethal time (LT) were calculated using probit analysis. The results revealed that increase of conidial density of each fungi species caused more mortality of C. gestroi. All fungi species could cause mortality of C. gestroi more than 80% even with the density of 5x106 conidia/ml, however M. brunneum could causing mortality more than 80% at density of conidia as low as 5x105 conidia/ml. Based on the probit analysis, the value of LC50 and LT50 with contact method were calculated at 1.8 x 105 conidia/ml and 2.01 (1.52 ~ 2.40) days respectively.